Growth of Amorphous Silicon Germanium (a-SiGe:H) Alloys Thin Film by PECVD - Mursal Mursal; A. Supu; I. Usman; T. Winata; Sukirno Sukirno; M. Barmawi (Institut Teknologi Bandung, 2004)
Hydrogenated amorphous silicon-germanium (a-SiGe:H) alloys thin films had been grown by Plasma Enhanced Chemical Vapor Deposition (PECVD) method. The films were grown on corning glass # 7059 from a gas mixture of silane (SiH4) and germane (GeH4) 10% diluted in hydrogen (H2). UV-VIS-NIR spectra analysis of a-SiGe:H alloys thin films showed that the sub-bandgap absorption α(hν) spectra of a-SiGe:H alloys shift to lower photon energy with increasing in GeH4 flow rate. The optical bandgap of a-SiGe:H alloy decreased non linearly from 0.94 eV – 0.75 eV with increasing in GeH4 flow rate from 2.5 sccm – 25 sccm. The photo-sensitivity (σph/σd) of a-SiGe:H thin films were improved as the optical bandgap (Eopt) increased.